2020
DOI: 10.1146/annurev-publhealth-040119-094043
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electronic Cigarettes on Indoor Air Quality and Health

Abstract: With the rapid increase in electronic cigarette (e-cig) users worldwide, secondhand exposure to e-cig aerosols has become a serious public health concern. We summarize the evidence on the effects of e-cigs on indoor air quality, chemical compositions of mainstream and secondhand e-cig aerosols, and associated respiratory and cardiovascular effects. The use of e-cigs in indoor environments leads to high levels of fine and ultrafine particles similar to tobacco cigarettes (t-cigs). Concentrations of chemical com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 135 publications
0
39
0
Order By: Relevance
“…Namely, the combustion of the liquid components to form a variety of potential toxins such as formaldehyde, acetaldehyde, propanol, carbon monoxide, acrolein, o-methyl benzaldehyde, nitrosamines, limonene, radical species, and other chemicals coupled with inhalation of volatilized metal particles and metal carbonyl complexes 2 5 . Exposure to such compounds is associated with adverse health effects, such as the decline in cardiovascular health in smokers and potentially even to individuals exposed secondhand 6 , 7 . Numerous factors impact the extent to which these compounds form, such as the liquid composition, power output of the resistively-heated coil, puff duration, and the coil material and configuration 8 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Namely, the combustion of the liquid components to form a variety of potential toxins such as formaldehyde, acetaldehyde, propanol, carbon monoxide, acrolein, o-methyl benzaldehyde, nitrosamines, limonene, radical species, and other chemicals coupled with inhalation of volatilized metal particles and metal carbonyl complexes 2 5 . Exposure to such compounds is associated with adverse health effects, such as the decline in cardiovascular health in smokers and potentially even to individuals exposed secondhand 6 , 7 . Numerous factors impact the extent to which these compounds form, such as the liquid composition, power output of the resistively-heated coil, puff duration, and the coil material and configuration 8 11 .…”
Section: Introductionmentioning
confidence: 99%
“…E-cigs have become a popular alternative to tobacco cigarettes, but the efficacy of e-cigs as smoking cessation aids remains inconclusive (Hartmann-Boyce, Begh, and Aveyard 2018;Malas et al 2016). A number of recent studies (Chun et al 2017;Polosa and Caponnetto 2016) have reported the potential toxicity of e-cig aerosols even though they typically contain lower levels of toxic chemicals than tobacco smoke (Li et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Although labeled as "a safer t-cig alternative," studies have shown that the use of e-cigs can worsen indoor air quality and may adversely affect human health (Li et al, 2020b). In mainstream e-cig aerosols, mean particle number concentrations (PNCs) on the order of 10 7 to 10 9 particles cm -3 have been reported in chamber studies (Ingebrethsen et al, 2012;Fuoco et al, 2014;Mikheev et al, 2016;Zhao et al, 2016) and mean PM 2.5 concentrations of 184 µg m -3 have been reported (Lee et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid increase in e-cig users, secondhand involuntary exposure to exhaled e-cig aerosols has become a serious public health concern (Li et al, 2020b). Indoor PNC of 10 4 to 10 5 particles cm -3 and PM 2.5 concentrations of 152-375 µg m -3 were reported in real-world studies (Czogala et al, 2014;Schober et al, 2014;Zhao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%